2010
DOI: 10.1002/mpr.305
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the German version of the Health of the Nation Outcome Scales (HoNOS‐D): a clinician‐rating for the differential assessment of the severity of mental disorders

Abstract: The Health of the Nation Outcome Scales (HoNOS) is an internationally-established clinician-rating instrument for the differential assessment of the severity of patients with mental disorders. The aim of this study was to examine the validity of the German version of the HoNOS (HoNOS-D). Evaluation of validity, including factor validity, convergent and discriminant validity and sensitivity to change, was conducted on a large, virtually representative, clinical sample of patients with mental disorders in inpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 38 publications
1
36
0
1
Order By: Relevance
“…In our sample, HoNOS sensitivity to change assessed by rating patients at admission and discharge (table 3) shows limitations in comparison with the CGI. Comparable to Audin et al [32] and Andreas et al [16], items 7 and 10 showed medium values, and the majority of the items and the HoNOS total score proved to be moderately sensitive to change, although our sample differs from their sample with regard to 37% of the participants having a schizophrenia diagnosis. Item 11 (‘residential problems’) has to be understood in the context of the average duration of treatment (30 days), changes in this timeframe not being likely.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In our sample, HoNOS sensitivity to change assessed by rating patients at admission and discharge (table 3) shows limitations in comparison with the CGI. Comparable to Audin et al [32] and Andreas et al [16], items 7 and 10 showed medium values, and the majority of the items and the HoNOS total score proved to be moderately sensitive to change, although our sample differs from their sample with regard to 37% of the participants having a schizophrenia diagnosis. Item 11 (‘residential problems’) has to be understood in the context of the average duration of treatment (30 days), changes in this timeframe not being likely.…”
Section: Discussionmentioning
confidence: 77%
“…It was suggested that the scale could be subdivided into 4 subscales (‘behavioral problems’, ‘impairment’, ‘symptomatic problems’ and ‘social problems’). However, there is not really much evidence that subscale scores are reliable [14,16,25,26]. Therefore, we only used the HoNOS-D main score and single items for further calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, further specific external criteria for the validation of single items were not included in this study (e.g., Brief Psychiatric Rating Scale [Overall & Gorham, 1976] or Addiction Severity Index [Mäkela, 2004;McLellan et al, 1992]). However, in another study, we examined the validity of the German version of the HoNOS in inpatients with a widespread of mental disorders (Andreas et al, 2010). Evaluation of validity, including factor validity, convergent and discriminant validity, and sensitivity to change, was conducted on a large, virtually representative, clinical sample of patients with mental disorders in inpatient psychotherapy (Study 1, N = 3,169).…”
Section: Discussionmentioning
confidence: 99%
“…In line with international developments and due to the lack of suitable national clinician-rating instruments for the differential assessment of severity, the HoNOS was translated into German with authorization from the test authors. The translation process and first empirical results on the practicability, reliability, and validity have been previously described elsewhere (Andreas et al, 2007;Andreas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%